2016
DOI: 10.1039/c6ta08198c
|View full text |Cite
|
Sign up to set email alerts
|

Structure design of NiCo2O4 electrodes for high performance pseudocapacitors and lithium-ion batteries

Abstract: An ultralight nickel scaffold is designed to enhance the electrochemical performance of NiCo2O4 nanowire electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 52 publications
2
29
1
Order By: Relevance
“…[42] Simultaneously,t he main reductionp eaks are shifted to higherp otentials at 0.79 V and 1.67 V, suggesting the existence of ap ossible activation process initially and the inactivation of the NiCoO 2 duringt he first cycle. [43][44][45] During the next anodic loops, two peaks appear at 1.57 Vand 2.35 V, which representst he oxidation of metallicN ia nd Co to NiO and CoO. [46,47] The electrode reactions can be explained by Equations (1)-(3), which correspond to the cyclic voltammetry resultsa nd as imilar reaction reported previously.…”
supporting
confidence: 66%
“…[42] Simultaneously,t he main reductionp eaks are shifted to higherp otentials at 0.79 V and 1.67 V, suggesting the existence of ap ossible activation process initially and the inactivation of the NiCoO 2 duringt he first cycle. [43][44][45] During the next anodic loops, two peaks appear at 1.57 Vand 2.35 V, which representst he oxidation of metallicN ia nd Co to NiO and CoO. [46,47] The electrode reactions can be explained by Equations (1)-(3), which correspond to the cyclic voltammetry resultsa nd as imilar reaction reported previously.…”
supporting
confidence: 66%
“…[15][16][17][18] Moreover, owing to the co-existence of two different metal cations in a single crystal structure, NiCo 2 O 4 can synergistically enhance the electrochemical performance as compared to the corresponding nickel oxides and cobalt oxides. 15,[19][20][21][22] For example, An et al demonstrated that the porous NiCo 2 O 4 nanowires exhibited higher capacitance than Co 3 O 4 with a similar structure. 19 More recently, Hu et al also reported that Co 3 O 4 / NiCo 2 O 4 double-shelled nanocages showed improved pseudocapacitance than the single-component Co 3 O 4 /Co 3 O 4 doubleshelled nanocages.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the similar structural requirements of electrode materials for Li-ion-based batteries and supercapacitors, the structure with excellent performance for one can be applied in the other one. For example, yolk-shelled Ni-Co mixed oxide nanoprisms, 15 NiCo 2 O 4 complex hollow spheres, 31 Mn-based mixed metal oxide hierarchical tubular structures, 20 and UNF@NiCo 2 O 4 composites 22 have been demonstrated to possess excellent performance in both fields. Thus, a material with large tunnels and mesopores, which has been proved to exhibit high performance for Li-O 2 batteries, 33 is a promising alternative electrode material for supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…In the conventional Li‐ion anodes, copper foil (≈10 µm thick) is universally employed to support a composite layer consisting of active materials, binders, and conductive agents . This laminate structure receives tremendous success for the intercalation materials because their volume changes are usually small and manageable by the calendared Cu foil and active material composite.…”
Section: Introductionmentioning
confidence: 99%